Imagery and expressive art as tools in counseling women with breast cancer - Cabale, Jo Anne F.; Rayco, Domingo R.; Nava, Fe Josefa G.; Oyzon, Maria Vanessa P. Lusung (Quezon City College of Education, University of the Philippines Diliman, 2013)
"This case study research sought to find out what emotions would be revealed by women with breast cancer in their drawings and if sessions in imagery and expressive art would be effective in releasing stress producing emotions, thus bring about some degree of psychological equilibrium. Four women with breast cancer undergoing treatments in a hospital participated in a six-session program developed by Barbara Ganim (1999) It explored the use of imagery and expressive art as a complementary treatment to help women with breast cancer weather treatments and to make life changes to cope with breast cancer. Its aim was to enable the expression of feelings so that the problems that come with breast cancer were put in proper perspective. Imagery and expressive art techniques uncovered the negative and positive emotions. The main negative emotions were: helplessness, pain and anger. The positive emotions were faith and hope. The pretest – posttest using Brief Stress and Coping Inventory (Rahe, 1998) yielded positive differences in their scores, namely, +57% and +8.27% for two women while the other two women with breast cancer had incomplete data. For the two women who had positive differences their scores showed that imagery and expressive art sessions helped them cope with living with breast cancer. They had made significant changes in their lives to help them cope with breast cancer and its treatments." --
Thesis
Keywords: Breast -- Cancer -- Patients -- Counseling of; Breast -- Cancer -- Patients -- Philippines -- Quezon City; Drawing -- Therapeutic use; Arts -- Therapeutic use